The women behind the door - Doyle, Roddy, 1958- (Viking, an imprint of Penguin Random House, 2024)
"A powerful, moving mother-daughter story filled with struggle and redemption by Booker-Prize winning author Roddy Doyle. At sixty-six, Paula Spencer--mother, grandmother, widow, addict, survivor--has finally started to live her life. She has a job at the dry cleaners she enjoys, her boyfriend Joe is a text away when she needs him, and her four children now have the healthy families and petty dramas that Paula could have only hoped for. Despite its ghosts, Paula has started to push her past aside. That is until her eldest, Nicola, turns up on her doorstep one day. Nicola is everything Paula wasn't--independent, affluent, a loving wife and mother, a "success"--but now she is suddenly determined to leave it all behind. She has left her family and come to stay. As Nicola gradually confides in Paula the secret that unleashed this moment of crisis, mother and daughter must untangle past memory, trauma, and revelations to confront what they mean to each other--and who they want to be. A timely and powerful novel of regrets, reparations, and reconciliations, The Women Behind the Door is a delicately devastating portrait of shame and the inescapable shadow it casts over families. Many readers will welcome the chance to reconnect with this strong, singular character whom we have seen in The Woman Who Walked into Doors and Paula Spencer, but all readers will be glad to have Paula in their life now"--